I assume you mean y = -6. The slope of this would be zero since it is a horizontal line. For the equation x = -6, the slope would be infinite since this is a vertical line.
It is slope intercept form. The equation for slope intercept form is y=mx+b which is like your equation y=5x+6
A normal slope-intercept form equation would read: y = mx + b The slope of an equation is also known as 'm'. The y-intercept would count as 'b'. So in a random equation such as: y= 5x + 6 '5' would be the slope and '6' would be the y-intercept.
It is as for example: y = 3x+6 whereas 3 is the slope and 6 is the y intercept
Equation: y-3 = -5(x-6) => y = -5x+33
It is: y = 6x+18 whereas 6 is the slope and 18 is the y intercept
Point: (-6, -2) Slope: 5 Equation: y = 5x+28
Slope: -5 Points: (6, 3) Equation: y = -5x+33
The straight line equation would depend on the slope which has not been given.
-1
If the y intercept is -6 then the equation is: y = -7x-6
This equation is in the slope-intercept form, y = mx + b, where the coefficient of x, m, is the slope and b is the y-intercept. Thus, in the equation y = 12x + 6, the slope is 12.
For example in the straight line equation of: y = 3x+6 then 3 is the slope and 6 is the y intercept
-36
-9
If you mean a slope of 6 and point of (-3, 5) then the equation is: y = 6x+23
As for example if the slope is 3 and the y intercept is 6 then the equation is: y=3x+6
Y = 6